The “Third Space” Concept in Intercultural Communication in Chinese - Djuraev, Dilshod Mamadiyarovich (The Lingua Spectrum, 2026)
Annotation Intercultural communication in the “third space” is not only a process and method of language teaching, but also the goal and outcome of language learning. Through this, we can see how essential it is to construct an intercultural “third space” in the context of globalization and the study of regional situations. Intercultural “third space” is a kind of intermediate field within which both the native language culture and the target language culture of a person engaged in intercultural communication are developed simultaneously, leading to the formation of a new culture. This enables speakers of different languages and cultural backgrounds to communicate freely and naturally within this space. The “third space” refers to a linguocultural space that emerges in the process of interaction between different cultures and is situated between two or more cultures. It incorporates certain features of the first and second cultural spaces, yet it is not identical to either of them. At the same time, it enables learners from diverse cultural backgrounds to communicate successfully. In recent years, the theory of the “Third Space” (第三空间) has become a popular topic in the field of international Chinese language education. Through interaction and communication with Chinese language learners, it can be observed that during the process of learning Chinese and engaging with Chinese culture, learners are gradually influenced by Chinese people and Chinese culture. However, they do not completely assimilate into or fully internalize Chinese culture. International students studying in China gradually integrate their native culture with Chinese culture over time, resulting in a phenomenon of cultural hybridity. The construction of such a hybrid cultural “Third Space”, which exists between the learners’ native culture and the target language culture, has a significant impact on foreign language learners. The conscious construction of an intercultural “Third Space” by foreign language learners is considered the ideal goal pursued in foreign language education.